Step-by-step explanation:
3/4 of 12
3/4 × 12 = 9
6/7 of 49
6/7 × 49 = 42
2/3 × 27 = 18
3/8 x 16 = 6
Base times height in math
Answer:
C
Step-by-step explanation:
according to the standard equation;
Y=mX+C
or, Y=4/5X +3
9514 1404 393
Answer:
x in {-6, -2, 4}
Step-by-step explanation:
The zero product rule tells you that a product will be zero if and only if one of the factors is zero. These binomial factors are zero when x has a value that is opposite the constant of the binomial.
x +6 = 0 ⇒ x = -6
x -4 = 0 ⇒ x = 4
x +2 = 0 ⇒ x = -2
The zeros of the function are the x-values -6, -2, and 4.